Evaluation of Bone Volume After Secondary Bone Grafting in Unilateral Alveolar Cleft Using Computer-Aided Engineering. - Hayato Nagashima; Yoshiaki Sakamoto; Hisao Ogata; Junpei Miyamoto; Masaki Yazawa; Kazuo Kishi (Cleft Palate Craniofacial Journal, 2014)
The purpose of this study was to evaluate the initial defect and the outcome of bone grafts for unilateral alveolar cleft. To determine the absorption of the bone graft in patients with unilateral cleft, computer-aided engineering (CAE) with multi-detector row computed tomography (MDCT) was used. MDCT scans of 29 patients were taken immediately preoperatively and at 1 month and 6 months postoperatively. The patients underwent bone grafting between 8 and 14 years of age using iliac crest bone grafts. Three-dimensional models were created in each period, and the defect at the alveolar cleft and volume of the bone graft were determined in each patient using CAE. Cleft volume and success of alveolar bone grafting were significantly correlated (P < .01). Alveolar clefts with cleft palate required more bone volume than those without cleft palate (P < .01), but the resorption rate did not significantly differ between alveolar clefts with and without cleft palate (0.48 ± 0.14 and 0.49 ± 0.18, respectively; P=. 93). In conclusion, three-dimensional reconstruction of bone grafts using CAE based on MDCT provides a valuable objective assessment of graft volume.